A cross-cultural comparison of climacteric symptoms, self-esteem, and perceived social support between Mosuo women and Han Chinese women. Issue 7 (July 2016) - Zhang, Ying; Zhao, Xudong; Leonhart, Rainer; Nadig, Maya; Hasenburg, Annette; Wirsching, Michael; Fritzsche, Kurt
Abstract: Objective: This cross-cultural study aimed to compare climacteric symptoms, self-esteem, and perceived social support between Mosuo and Han Chinese women, and to explore the interaction between culture and climacteric symptoms. Mosuo is a Chinese minority group with a matriarchal structure, and Han Chinese is the majority ethnic group in China with a patriarchal structure. Methods: Through convenience sampling, 54 Mosuo women and 52 Han Chinese women between 40 and 60 years of age completed the sociodemographic questionnaire, the Menopause Rating Scale, the Self-Esteem Scale, and the Perceived Social Support Scale. Results: Compared with Han Chinese women, Mosuo women scored lower on the psychological ( P  < 0.001) and the somato-vegetative ( P  = 0.047) subscales of the Menopause Rating Scale, but higher on the Self-Esteem Scale ( P  = 0.006) and the "support from family" subscale of the Perceived Social Support Scale ( P  = 0.004). Multiple linear regressions indicated that minority ethnicity (β = 0.207, P  = 0.016) was one of the predictive variables of psychological symptoms severity. Referring to the severity of all symptoms, predictive variables were: perceived support from family (β = −0.210, P  = 0.017); self-esteem (β = 0.320, P  < 0.001); previous history of premenstrual syndrome (β = 0.293, P  < 0.001); number of family members (β = −0.229, P  = 0.003); and family income (β = −0.173, P  = 0.028). Conclusions: Differences in climacteric symptoms were found between two groups. Cultural variables such as familial structure, women's self-esteem, and perceived social support were correlated with symptomatology.